A retrospective study on factors related to in-hospital mortality among patients with COVID-19, March 2020 to November 2021 - Zinellu, Elisabetta; Fois, Sara S; Di Lorenzo, Biagio; Zoroddu, Stefano; Pau, Maria C; Tassi, Lorenzo; Piras, Barbara; Fois, Alessandro G; Carru, Ciriaco; Mangoni, Arduino A; Zinellu, Angelo; Pirina, Pietro (The Journal of Infection in Developing Countries, 2025)
Introduction: Four years since the pandemic was declared, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains an important cause of illness around the world. Although many countries were able to overcome the health crisis at its peak, there are still individuals at high risk of a severe course of coronavirus disease 2019 (COVID-19). Therefore, it is important to continue research on the factors that could predict disease severity and adverse outcomes. Methodology: We conducted a retrospective study on 171 consecutive hospitalized cases of COVID-19 from March 2020 to November 2021. Past medical history, drug history, clinical and laboratory parameters on admission, and the choice of treatment during hospital stay were obtained and associated with in-hospital mortality. Results: Older age was significantly associated with mortality. Non-survivors also showed a significantly lower PaO2/FiO2 (P/F) ratio at the time of hospital admission; a lower lymphocyte count; and increased levels of white blood cell count, C-reactive protein (CRP), lactate dehydrogenase (LDH), D-dimer, and creatinine. Significant differences were also observed with regards to both long-term medications and treatments administered during hospital stay. Conclusions: Our findings highlight the importance of age, clinical features, biochemical biomarkers, and therapeutic interventions in predicting COVID-19 disease severity and outcomes.